The Revealing Accounting For Waste Entrepreneurs Seen From Sharia Perspective - Dyatri Utami Arina Absari (International Journal of Economic Research and Financial Accounting, 2024)
Garbage is a problem that must be faced by the public due to discharges of waste is generated from human activities unused (Yansen & Arnatha, 2012). Waste problem is to encourage the growth Of public awareness to participate take part in waste management (Utami & Indrasti, 2008). According to (Adnan, 1995: 47) side of science, accounting is actually a domain "muamalah" in Islamic studies. That is, given the ability of the human mind to develop it (Harahap, 2004). Shariah is thus selling goods rosok automatically be referred to as merchandise goods rosok is a rosok used items, but with the up to date and efficient pengelolahan rosok goods has had a good selling price without compromising the quality and quantity (Sholichudin 2009). This type of method that will be used in this study is aqualitative research study based phenomenology. Qualitative research is research that aims to understand the social reality, which is to see the world from what it is, not the world should be, which have open minded nature. Based on interviews with searchers and collect waste, it acquired the meaning of accounting is A recording of value responsibility, and a sense of divinity in the form of income and sustenance of Allah without gharar that bring a sense of inner satisfaction.